Menjinakkan Si Jago Merah - Gilarsi, Eriyano W; Husain, Sarkawi B (Masyarakat Sejarawan Indonesia, 2019)
This article mainly discussing about forest fire in Mojokerto in 1890-1939. Forest fire became a serious problem in colonial era, especially after the forest undergone the degradation as the result of cultuurstelsel. The forest in Mojokerto became one of the forest that is often gets burned by the forest fire. By using historical method, the author is attempting to analyze the attempts made by Nederlandsch-IndiÃ«government and communities in dealing with forest fire in Mojokerto. All of the data that is used in this research are based on various official publication from Nederlandsch-IndiÃ« government, newspaper published in colonial era, books of references, journal, and theses. Beside reforestation, fire outage is one of the efforts made to prevent forest fire. As a result of these efforts, a new special unit called De Bosch-brandweer was formed. However, due to repeated forest fire activity, a preventive effort such as improving the law that regulates forest activities appeared, including the creation of forest fire free lane â€œgordel wegâ€.